Autoimmune Enteric Neuropathies: A Narrative Review of Diagnostic Strategies and Immunotherapeutic Approaches for Gastrointestinal Dysmotility - Malapati, Sai Nikhitha (Eastern Journal of Medical Sciences, 2025)
Background: Autoimmune enteric neuropathies (AENs) are rare but potentially reversible causes of severe gastrointestinal dysmotility, frequently overlooked or misdiagnosed as functional or obstructive disorders. They often present as gastroparesis, chronic constipation, or intestinal pseudo-obstruction, leading to diagnostic delays and poor outcomes. Methods: We conducted a narrative review of the literature using PubMed, EMBASE, and Scopus (2000–2024), focusing on clinical, diagnostic, immunologic, and therapeutic data relevant to AEN. Search terms included “autoimmune enteric neuropathy,” “enteric ganglionitis,” “gastrointestinal dysmotility,” “immunotherapy,” and “paraneoplastic.” Results: AENs require a multimodal diagnostic approach, including anti-neuronal antibody testing (e.g., anti-Hu, anti-CV2), full-thickness intestinal biopsy, and exclusion of structural disease. Paraneoplastic forms, especially those associated with small cell lung carcinoma, and idiopathic variants remain the most common. Immunomodulatory therapies such as corticosteroids, intravenous immunoglobulin (IVIG), azathioprine, and rituximab have shown variable success, particularly when initiated early. Recent advances include trials of subcutaneous immunoglobulin, interleukin inhibitors, JAK inhibitors, and neuro-regenerative strategies. However, evidence remains limited, predominantly comprising case reports and small series. Conclusions: This review highlights AENs as an under-recognized but treatable cause of gastrointestinal dysmotility, with emerging therapeutic strategies showing promise in refractory cases. Critical gaps persist regarding diagnostic consensus, biomarker validation, and standardized treatment. Multidisciplinary approaches, earlier serological testing, and prospective clinical trials are urgently needed. Enhancing clinician awareness could transform outcomes in.